A class A β-lactamase produced by borderline oxacillin-resistant Staphylococcus aureus hydrolyses oxacillin. (September 2020) - Nomura, Ryo; Nakaminami, Hidemasa; Takasao, Kotaro; Muramatsu, Shuna; Kato, Yuji; Wajima, Takeaki; Noguchi, Norihisa
Highlights: S. aureus carrying blaZ derived from BORSA decreased susceptibility to oxacillin. BlaZ of BORSA and MSSA were classified into serological types A and C, respectively. BlaZ (BORSA) was found to hydrolyse oxacillin faster than BlaZ (MSSA). Ala-112 of BlaZ (BORSA) plays an important role in the hydrolysis of oxacillin. A staphylococcal penicillinase may act as an extended spectrum β-lactamase. Abstract: Objectives: Recently, mecA -negative Staphylococcus aureus strains with decreased susceptibility to oxacillin have been sporadically reported worldwide. They have been called borderline oxacillin-resistant S. aureus (BORSA). S. aureus β-lactamase (BlaZ), which is encoded by the blaZ gene, is categorized as a class A β-lactamase (penicillinase); hence, its hydrolytic activity against oxacillin, cephems, and carbapenems is low. The aim of this study was to clarify the mechanism of oxacillin resistance in BORSA. Methods: Clinical BORSA (MIC = 1 μg/mL) and methicillin-susceptible S. aureus (MSSA; MIC = 0.25 μg/mL) isolates carrying blaZ were used. Amino acid sequencing, oxacillin susceptibility testing and evaluation of oxacillin hydrolysis activity were conducted. Results: The S. aureus RN4220 strain carrying blaZ derived from BORSA was found to have decreased susceptibility to oxacillin compared with a strain carrying blaZ from an MSSA strain. The BlaZ (BORSA) differentiated six amino acids (M10I, E112A, K193E, N196K, F203L and N207S) compared with BlaZ (MSSA). Based on the amino acid sequences, BlaZ (BORSA) and BlaZ (MSSA) were classified into different serological types A and C, respectively. The recombinant BlaZ (BORSA) was found to hydrolyse oxacillin faster than BlaZ (MSSA). Additionally, site-directed mutagenesis showed that an alanine at position 112 of the amino acid sequence of BlaZ (BORSA) plays an important role in the hydrolysis of oxacillin. Conclusion: Our findings strongly suggest that type A staphylococcal β-lactamase acts as an extended-spectrum β-lactamase and contributes to borderline resistance to oxacillin in S. aureus .